Implikasi Media Pohon Kebajikan terhadap Pemahaman Materi Siswa Kelas 1 pada Pembelajaran PPKn di MI Nurul Ulum Bojonegoro - Fitria, Sufatul; Mansyuri, Arif (Awwaliyah: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2023)
This study aims to describe the process of using virtue tree media in increasing students' understanding of class 1 MI Nurul Ulum Bojonegoro material. This study aims to determine the effect of virtue tree media on understanding PPKn material and the differences in the results of using virtue tree media on class 1 students' understanding of MI Nurul Ulum Bojonegoro. This study uses a type of quantitative experimental research. The object of this research is grade 1 students, amounting to 30 students. Data collection techniques using tests, interviews, and documentation. The research instrument used the pre test and post test. The data analysis technique uses the dependent T-test which consists of normality and correlation tests. Based on the results of the research, analysis and discussion, it was obtained that the normality test for the Shapiro-Wilk obtained a sig value of 0.098 > 0.05 in class A and 0.131 > 0.05, which means that it is normally distributed. While the dependent t-test obtained a significance of 0.000 <0.05 which indicates the influence of the virtue tree on the understanding of PPKn material for grade 1 students. Based on the results of the study, it can be concluded that the media of virtue trees influences the understanding of grade 1 students MI Nurul Ulum Bojonegoro.